2018
DOI: 10.3389/fmicb.2018.00121
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Traits Are More Important than Stress-Tolerance Traits in a Cadmium-Contaminated Rhizosphere: A Role for Trait Theory in Microbial Ecology

Abstract: Understanding how biotic and abiotic factors govern the assembly of rhizosphere-microbial communities is a long-standing goal in microbial ecology. In phytoremediation research, where plants are used to remediate heavy metal-contaminated soils, a deeper understanding of rhizosphere-microbial ecology is needed to fully exploit the potential of microbial-assisted phytoremediation. This study investigated whether Grime's competitor/stress-tolerator/ruderal (CSR) theory could be used to describe the impact of cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 61 publications
3
51
0
Order By: Relevance
“…However, meta-analyses of microbial communities to infer CSR strategies can be challenging due to 83 the different factors related to experimental design and techniques employed across different studies, 84 which could heavily affect the observations in comparison. Recent studies on soil-bacterial 85 communities in cadmium-contaminated rhizospheres (Wood et al 2018) and tillage-disturbed fields 86 (Schmidt et al 2018) also suggested the applicability of the CSR approach to soil-microbial 87 communities. To our knowledge, the CSR framework has not yet been employed within a single study 88 to changes in microbial communities upon disturbance in any microbiome other than soil.…”
Section: Introduction 44mentioning
confidence: 99%
“…However, meta-analyses of microbial communities to infer CSR strategies can be challenging due to 83 the different factors related to experimental design and techniques employed across different studies, 84 which could heavily affect the observations in comparison. Recent studies on soil-bacterial 85 communities in cadmium-contaminated rhizospheres (Wood et al 2018) and tillage-disturbed fields 86 (Schmidt et al 2018) also suggested the applicability of the CSR approach to soil-microbial 87 communities. To our knowledge, the CSR framework has not yet been employed within a single study 88 to changes in microbial communities upon disturbance in any microbiome other than soil.…”
Section: Introduction 44mentioning
confidence: 99%
“…This tradeoff is reiterated by the absence of scenarios of communities excelling in both traits (figure 2, upper right). However, in certain communities lower resource acquisition costs were accompanied with lower growth yields (Figure 2, lower left), where, it is plausible that either or both of these traits trade off with some other unmeasured trait, likely stress tolerance 15,19,20 . In support of this interpretation, we previously found lower growth rate and yield in acidic soils ( Figure S1-2) 15 highlighting much higher maintenance costs of acid stress tolerance in such soils.…”
mentioning
confidence: 99%
“…This classification was mostly based on microbial substrate preferences and growth rates and has since been widely applied in various contexts (Fierer et al, 2012;Thomson et al, 2013). Several recent efforts have also applied C-S-R life history strategies to microbial systems, particularly in the context of anthropogenic environmental change (Fierer, 2017;Ho et al, 2013;Krause et al, 2014;Wood et al, 2018). Ho et al (2013) classified methane-oxidising bacteria into C-S-R life strategies based on activity, recovery from disturbances, substrate utilization patterns and stress tolerance.…”
Section: Life History Concepts In Macroecologymentioning
confidence: 99%